The Effect of Compensation and Job Satisfaction on Performance of Waste Transporters at the Environmental Service in Ternate City - Karosa, Inda D G; Soleman, Marwan Man; Mustafa, Ikrima M (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Human Resources (HR) are assets that are very necessary for every organization in its efforts to achieve its goals. HR plays an important role in various organizational activities. Job satisfaction, which includes employee attitudes towards work, involves factors such as the work situation, cooperation between co-workers, acceptance of work challenges, and consideration of physical and psychological aspects. The aim of this research is to analyze the influence of compensation and job satisfaction on the performance of Waste Transporters at the Environmental Service. This research uses quantitative research methods using primary and secondary data. The sampling technique used was purposive sampling. Primary data was collected through questionnaires and interviews conducted with 102 research respondents. Secondary data sources include information from journals, books, and data obtained from the Ternate City Environmental Service. The research timeline starts from July 2023 to September 2023. The test results show that the job satisfaction variable has a negative and significant effect on labor performance. This suggests that addressing and increasing job satisfaction may be important for improving overall labor performance.